2008
DOI: 10.1371/journal.pone.0003744
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Niche of the 2003 West Nile Virus Epidemic in the Northern Great Plains of the United States

Abstract: BackgroundThe incidence of West Nile virus (WNv) has remained high in the northern Great Plains compared to the rest of the United States. However, the reasons for the sustained high risk of WNv transmission in this region have not been determined. To assess the environmental drivers of WNv in the northern Great Plains, we analyzed the county-level spatial pattern of human cases during the 2003 epidemic across a seven-state region.Methodology/Principal FindingsCounty-level data on WNv cases were examined using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
82
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(89 citation statements)
references
References 38 publications
7
82
0
Order By: Relevance
“…The high WNV rates in the Northern Great Plains region likely dampened potential significant clusters from other regions as the Anselin Local Moran's I test considers the global population mean in its local calculations. States in the northern Great Plains have been shown to have high WNV rates with consistent spatial clustering, especially in eastern Colorado and throughout Nebraska, South Dakota and North Dakota (Wimberly et al, 2008;Sugumaran et al, 2009;DeGroote and Sugumaran, 2012). South Dakota, in the Northern Great Plains region, has had the highest average incidence of WNV neuroinvasive disease in the USA since 2004 (Wimberly et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high WNV rates in the Northern Great Plains region likely dampened potential significant clusters from other regions as the Anselin Local Moran's I test considers the global population mean in its local calculations. States in the northern Great Plains have been shown to have high WNV rates with consistent spatial clustering, especially in eastern Colorado and throughout Nebraska, South Dakota and North Dakota (Wimberly et al, 2008;Sugumaran et al, 2009;DeGroote and Sugumaran, 2012). South Dakota, in the Northern Great Plains region, has had the highest average incidence of WNV neuroinvasive disease in the USA since 2004 (Wimberly et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In Iowa, inconsistent inter-annual climatic relationships were found in relation to WNV incidence (DeGroote et al, 2008). In the Great Plains region, it was suggested that a May-July precipitation of approximately 200 mm reflects optimum conditions for WNV amplification (Wimberly et al, 2008). In Mississippi, an inverse relationship between countylevel WNV risk and total annual rainfall during the previous year was demonstrated (Wang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…16 We recognize that there are compositional differences in land cover and human population between counties, but our data and that of other researchers in the field indicate that aggregating these data at a county resolution is a viable method for these analyses. 3,9,[17][18][19] Human disease case data (2002-2008) with a county resolution, including meningitis/encephalitis, WN fever, and other clinical/unspecified cases as defined by the Centers for Disease Control and Prevention (CDC), 20 were collated from the US Geological Survey Disease Maps webpage. 21 Alaska and Hawaii were excluded because human WNV disease cases have not been reported from these states.…”
Section: Methodsmentioning
confidence: 99%
“…Wimberly et al (2008) found a quadratic relationship between the rate of human WNv diseases in 2003 and May-July precipitation of 2002 in the Great Plains in USA, with the 2003 rate of human WNv diseases decreasing when total May-July precipitation reached beyond 200 mm. In addition, the land use and land cover of a region are unlikely to change at a large spatial scale in the short term (e.g., 1-2 years) unless catastrophic disasters occur.…”
Section: Discussionmentioning
confidence: 96%